Self-activated epitaxial growth of ScN films from molecular nitrogen at low temperatures - Chandrashekhar P. Savant; Anita Verma; Thai-Son Nguyen; Len van Deurzen; Yu-Hsin Chen; Zhiren He; Salva S. Rezaie; Jakob Gollwitzer; Benjamin Gregory; Suchismita Sarker; Jacob Ruff; Guru Khalsa; et al. (APL Materials)
Unlike naturally occurring oxide crystals such as ruby and gemstones, there are no naturally occurring nitride crystals because the triple bond of the nitrogen molecule is one of the strongest bonds in nature. Here, we report that when the transition metal scandium is subjected to molecular nitrogen, it self-catalyzes to break the nitrogen triple bond to form highly crystalline layers of ScN, a semiconductor. This reaction proceeds even at room temperature. Self-activated ScN films have a twin cubic crystal structure, atomic layering, and electronic and optical properties comparable to plasma-based methods. We extend our research to showcase Sc’s scavenging effect and demonstrate self-activated ScN growth under various growth conditions and on technologically significant substrates, such as 6H–SiC, AlN, and GaN. Ab initio calculations elucidate an energetically efficient pathway for the self-activated growth of crystalline ScN films from molecular N2. The findings open a new pathway to ultralow-energy synthesis of crystalline nitride semiconductor layers and beyond.